2012
DOI: 10.1021/jf2050763
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A Prevents Adipocyte Differentiation and Lipogenesis via Suppression of Peroxisome Proliferator-Activated Receptor γ and Sterol Regulatory Element-Binding Protein Pathways

Abstract: Licochalcone A (LA) has been shown to exert multiple pharmacological effects, including anti-inflammatory, antiparasitic, antifungal, anticancer, and osteogenic activities. The present study investigated the ability of LA to suppress the differentiation of 3T3-L1 preadipocytes, and its antiobesity activity was explored using high fat diet (HFD)-fed ICR mice. During the terminal differentiation process, 3T3-L1 preadipocytes were treated with LA, and the lipid contents were quantified along with any changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The anti-obesity properties of licochalcone A, a natural phenol also from the root of Glycyrrhiza glabra, were assessed in 3T3-L1 adipocytes and resulted in reduced lipid accumulation and down regulation of the expression of key adipogenic genes and receptors [198]. The analysis in high-fat diet induced obese mice confirmed the anti-obesity effect of licochalcone A by decreasing their body weight and plasma triglyceride, and cholesterol level [198].…”
Section: From Rootsmentioning
confidence: 86%
“…The anti-obesity properties of licochalcone A, a natural phenol also from the root of Glycyrrhiza glabra, were assessed in 3T3-L1 adipocytes and resulted in reduced lipid accumulation and down regulation of the expression of key adipogenic genes and receptors [198]. The analysis in high-fat diet induced obese mice confirmed the anti-obesity effect of licochalcone A by decreasing their body weight and plasma triglyceride, and cholesterol level [198].…”
Section: From Rootsmentioning
confidence: 86%
“…The results were relatively consistent with the results from normal adult mice that were fed a high-fat diet. 21,22) Concerning the expression of CYP species in the liver, the expression of CYP3A, CYP1A, CYP2C, and CYP2D in the mothers that consumed a high-fat diet during pregnancy was not different from that in the control group, but the expression of CYP2E in the HF group was increased compared to the control group (Fig. 3).…”
Section: The Effect Of High-fat Diet Consumption During Pregnancy On mentioning
confidence: 96%
“…Isoliquiritin apioside and isoliquiritigenin, as sources of pancreatic lipase (PL) inhibitors for preventing obesity, could lower the plasma total triglycerides and total cholesterol [111]. Licochalcone A had an inhibitory effect on adipocyte differentiation and lipogenesis via the downregulation of PPAR-c, CCAAT/enhancer binding protein α (C/EBPα), and sterol regulatory element-binding protein 1c (SREBP-1c) in 3T3-L1 preadipocytes [112]. And other results demonstrated that licochalcone A was effective to reduce obesity and could recover metabolic homeostasis by inducing adipocyte browning [113].…”
Section: Antidiabetic Activitymentioning
confidence: 99%